Changing Domesticity of Aedes aegypti in Northern Peninsular Malaysia: Reproductive Consequences and Potential Epidemiological Implications - Rahman, G.M. Saifur; Dieng, Hamady; Ahmad, Abu Hassan; Md Rawi, Che Salmah; Satho, Tomomitsu; Miake, Fumio; Ahmad, Hamdan (Research Gate, 2012)
Background